PENINGKATAN KESADARAN MASYARAKAT TERHADAP BUDAYA KESELAMATAN DAN KESEHATAN LINGKUNGAN DI BATU AJI BATAM - Arsyad Sumantika; Bahariandi Aji Prasetyo; Elsya Paskaria Loyda Tarigan; Hendy Rinaldy; Agi Zulin. H; Sri Zetli (PUAN INDONESIA, 2026)
The objective of this community service activity was to enhance public awareness and understanding of the significance of implementing occupational health and safety (OHS) practices in residential and domestic settings. The program was conducted in Batu Aji Residential Area, Batam City, from January to April 2026, targeting local residents and household heads. The implementation method employed a participatory approach through field observations, door-to-door socialization, direct counseling, interactive discussions, and the distribution of educational packages to the community. The observation results indicated that public awareness regarding environmental safety practices remained relatively low, particularly in terms of unsafe electrical installations, inadequate household waste management, and limited concern for environmental cleanliness. Following the implementation of the program, the community demonstrated improved understanding of safe electricity usage, the importance of maintaining environmental cleanliness, proper household waste management, and simple accident prevention measures within the household environment. The door-to-door socialization method was considered effective in enhancing communication and encouraging active community participation. This activity is expected to serve as an initial step toward fostering a sustainable